PERANCANGAN APLIKASI E-PARTNERSHIP MENGGUNAKAN METODE AGILE BERBASIS WEB PT. INDUSTRI TELEKOMUNIKASI INDONESIA (PERSERO) - Rahmi Rismayani Deri; Farhan Alfi Mubarok; M Dzuhur Islam (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
PT. The Indonesian Telecommunications Industry is a provider of products and services based on digital service innovation to answer business needs to facilitate automation in consumer company organizations. Every consumer/potential partner who wants to be part of a partnership at PT. The Indonesian Telecommunications Industry previously had to register as a partner manually using a paper registration form for prospective partners, besides that the required documents were still in the form of paper documents that could be lost at any time. The concept of Agile Software Development was coined by Kent Beck and 16 colleagues by stating that agile software development is a way of building software by doing it and helping others build it at once. Agile software development methods or agile methodology is a set of software development methodologies based on iterative development, where requirements and solutions develop through collaboration between organized teams Based on the stages of analysis of admin and user needs, it can be concluded that there are several things that must be considered and made carefully, including the programming structure, database specifications, and user interface design must be in accordance with The e-Partnership system is made to make it easier for companies to provide information about the procurement of goods or services and other informational information. As for partners of PT. The Indonesian Telecommunication Industry makes it easy to get information about procurement and other information. In addition, this system can make it easier for prospective partners to register to become partners online, because to access the main page of procurement information and other information can only be accessed by partners who already have an e-Partnership application account. Admin dashboard made to make it easier to update, add, and delete procurement information and other information. And the information will be informed through the e-Partnership website to the logged in partner.